The Influence of Consumers’ Purchase Intention Factors on Willingness to Pay for Renewable Energy; Mediating Effect of Attitude - Nazir, Mehrab; Tian, Jian (Frontiers in Energy Research, 2022)
Low market adoption has been a real challenge to Pakistan`s renewable energy growth. This research investigated the factors that influence the intention to use renewable energy in Pakistan. This research was conducted to examine the influences of renewable energy and marketing factors on purchase intention through attitude. It analyzed seven concepts: social media exposure, relative advantage, ease of use, awareness, cost, attitude, and purchase intention and deliberated their relationships. The conceptual framework is based on the theory of planned behavior and the unified theory of acceptance. The primary purpose of this study is to examine the influence of (social media exposure, relative advantage, ease of use, awareness, and cost) on purchase intention with the indirect effect of attitude. Proposed hypotheses have been tested using structured questionnaires through SPSS (AMOS) based on a sample of 497 respondents from Pakistan. Structural equation modeling technique was used to analyze the studied variables’ relationships (social media exposure, relative advantage, ease of use, and ease of use, awareness, and cost) and attitude with purchase intention. Study findings show that attitude has a major mediating effect on the relationship between purchase intention and (social media exposure, relative advantage, ease of use, awareness, and cost). The main findings revealed interesting consumer purchase intention regarding renewable energy technology. The results showed a significant positive relationship between influential determinants (social media exposure, relative advantage, ease of use, awareness, and cost) and purchase intention towards the use of renewable energy technology. This study suggests that these marketing approaches can be used as a brand marketing strategy to enhance customer purchase intention. The study’s findings will help in making decision in the renewable energy sub-sector. Furthermore, the findings of this study could be used as a reference by the government when making decisions about renewable energy deployment.